Pharmacognostic Study and Sedative Activity of Bryophyllum pinnatum Stem Methanol Extract and Fractions - Okoye, Kosisochukwu Frances; Anowi, Fredrick Chinedu; Ejiofor, InnocentMary IfedibaluChukwu; Ololade, Olanrewaju Mary (Sciences of Phytochemistry, 2023)
Insomnia is known as sleep insufficiency and is considered a capital public health concern. Bryophyllum pinnatum which belongs to the family Grassulaceae is used in folkloric medicine to treat various kind of ailment. The aim of the study was to undertake a pharmacognostic study of the stem and determine the sedative/hypnotic ability of the methanol extract and fraction of the stem. The physicochemical analysis indicated moisture content (12.68%), total ash (3.75%), acid insoluble ash (2.60%), water soluble ash (2.00%), water soluble extractive (6.02%) and alcohol soluble extractive (10.80%). The organoleptic evaluation of the powdered leaves revealed an odorless, green plant with bitter taste. The microscopic analysis of the leaf revealed palisade cell, spongy cell, stoma, collenchyma, xylem tissue, phloem tissue. The transverse section of the stem revealed epidermis, endodermis, xylem and cortex. The acute toxicity result revealed that Picralima nitida had no adverse effect in Wistar mice. The result showed that ethyl acetate fraction had sedative/hypnotic ability, affected the level of liver enzymes (ALT, AST, ALP), improved kidney function, and insignificantly increased body weight of mice. This study demonstrated that B. pinnatum could be an alternative medicine in pharmacological treatment of insomnia.